Chronology and documentary handbook of the State of Arizona. - Trover, Ellen Lloyd (Dobbs Ferry, N.Y. : Oceana Publications, 1972)
Contains a chronology of historical events from 1526 to 1970, a directory of political figures, an outline of the State constitution, and copies of five historical documents.
include Bibliographical reference and index.
Keywords: Arizona -- History -- Chronology; Arizona -- History -- Sources; Arizona -- History